Reliability, acceptability, validity and responsiveness of the CHU9D and PedsQL in the measurement of quality of life in children and adolescents with overweight and obesity - Hayes, Alison; Raghunandan, Rakhee; Killedar, Anagha; Smith, Sarah; Cvejic, Erin; Howell, Martin; Petrou, Stavros; Lancsar, Emily; Wong, Germaine; Craig, Jonathan; Howard, Kirsten (My University, 2023)
The Paediatric Quality of life Inventory (PedsQLTM) Generic Core Scales and the Child Health Utilities 9 Dimensions (CHU9D) are two paediatric health-related quality of life (HRQoL) measures commonly used in overweight and obesity research. However, no studies have comprehensively established the psychometric properties of these instruments in the context of paediatric overweight and obesity. The aim of this study was to assess the reliability, acceptability, validity and responsiveness of the PedsQL and the CHU9D in the measurement of HRQoL among children and adolescents living with overweight and obesity.
International Journal of Obesity
Keywords: Childhood and child development; Health and wellbeing